Field notes and Ted LaGrange letter to James J. Dinsmore, June 20, 1986 - LaGrange, Tedet al (1986)
List of birds and locations contributed by Ted LaGrange. The field notes consist of birds and locations observed for spring and summer 1986. Included with the field notes is a note from Ted LaGrange to James J. Dinsmore regarding the observations. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1986. Epson - sheet feed/flatbed